Peningkatan Hasil Belajar Materi Sosialisasi dalam Masyarakat Menggunakan Media SEMASA Pada Peserta Didik Kelas VII SMP Negeri 29 Surabaya - Latifa, Rima; Sriviyantiningrum, Nurul; Murtini, Sri (Innovative: Journal Of Social Science Research, 2024)
The purpose of this study was to use SEMASA media on the content of Socialization in the Community to improve student learning outcomes. Students of class VII E of SMP Negeri 29 Surabaya became the subjects of the study. This study used Collaborative Classroom Action Research (CAR) as its research methodology. This study was conducted in two cycles, with each cycle having four stages: planning, implementation, observation, and reflection. As many as 72.3% of students in cycle I successfully completed the learning outcomes of students classically, while in cycle II as many as 83.7% of students completed the learning outcomes. Based on the results of the study, it can be concluded that the use of SEMASA media can improve the learning outcomes of students in class VII E of SMP Negeri 29 Surabaya.